PERAN ORGANISASI IKATAN PELAJAR MUHAMMADIYAH DALAM PENDIDIKAN AKHLAK PELAJAR DI MUHAMMADIYAH 13 SOLOKURO LAMONGAN: PERAN ORGANISASI IKATAN PELAJAR MUHAMMADIYAH DALAM PENDIDIKAN AKHLAK PELAJAR DI MUHAMMADIYAH 13 SOLOKURO LAMONGAN - Nashrudin Abdul Khair (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2023)
The backgound of this study is a student moral education in the organization of Muhammadiyah Student Association; what is the problem of this researcher is what the activities of the Muhammadiyah Student Association in MTs. Muhammadiyah 13 Solokuro in order to help Muhammadiyah student moral education and how the role of the Muhammadiyah Student Association to student moral education in MTs Muhammadiyah 13 Solokuro Lamongan. The purpose of this study was to determine the activities of the Muhammadiyaah Student Association at MTs. Muhammadiyah 13 Solokuro in order to help Muhammadiyah student moral education and to determine the role of the Muhammadiyah Student Association against student moral education in MTs. Muhammadiyah 13 Solokuro Lamongan. The research method used is to use qualitative qualitative approach to be able to know how IPM MTs Muhammadiyah 13 Solokuro to guide the method of interaction is now good with high school and community. The data collection method used is observations involved, a semi-structured interview. The results showed that: (1) IPM (Muhammadiyah Student Association) MTs Muhammadiyah 13 Solokuro played an important role in student moral education. With this IPM, the lack of good student morals can convert to better, although not 100% but from the results of the guidance and work programs implemented by IPM can condition students for the better than before. (2) There are various types of IPM (Muhammadiyah Student Association) MTs Muhammadiyah 13 Solokuro which is related to student moral education. The type of activity is to include Qur’an Guidance, Islamic Studies, Leadership Training, Journalism Training and so on.